2007
DOI: 10.1111/j.1365-2621.2007.01286.x
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity of tangerine and lemon juices as a function of temperature and concentration

Abstract: Viscosities of two fruit (lemon and tangerine) juices have been measured with a capillary flow technique. Measurements were made in the temperature range from 303 to 393 K. The range of concentration was between 15 and 40°Brix for tangerine juice and between 17 and 45°Brix for the lemon juice. The total uncertainty of viscosity and temperature measurements was estimated to be <0.5% at low concentrations and up to 1.5% at high concentrations and 0.025 K, respectively. The effect of temperature and concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Changing temperature from 30 to 40 °C decreased standard‐fouling intensity by 16%. As reported in several works (Wang et al ., ; Magerramov et al ., ,b), feed viscosity is reduced by increasing temperature; therefore, permeate flux increased during membrane treatment with the increase in temperature. Mathematical modelling of fluid behaviour in microfiltration systems by Mirsaeedghazi et al .…”
Section: Resultsmentioning
confidence: 99%
“…Changing temperature from 30 to 40 °C decreased standard‐fouling intensity by 16%. As reported in several works (Wang et al ., ; Magerramov et al ., ,b), feed viscosity is reduced by increasing temperature; therefore, permeate flux increased during membrane treatment with the increase in temperature. Mathematical modelling of fluid behaviour in microfiltration systems by Mirsaeedghazi et al .…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that polyacrylonitrile degrades and nitriles hydrolyze completely in water at 210 o C for 3 hours [7]. The hydrolysis solutions contain carboxylic acid, ammonium carboxylate, amide, imide, et al There are many model equations to represent the relationship of the viscosity of polyelectrolyte solutions, temperature and concentration [8][9][10][11][12]. Some of those are listed in table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Viscosity is an important parameter of liquid foods (Magerramov et al ., 2007; Viswanath et al ., 2007). This property is widely considered and applied across industries to design food processes (Magerramov et al ., 2007); control qualities of food products (Silva et al ., 2017) and understand the rheological properties of food materials (Afoakwa et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Viscosity is an important parameter of liquid foods (Magerramov et al ., 2007; Viswanath et al ., 2007). This property is widely considered and applied across industries to design food processes (Magerramov et al ., 2007); control qualities of food products (Silva et al ., 2017) and understand the rheological properties of food materials (Afoakwa et al ., 2009). Especially, with respect to handling processes involving high viscous liquid medium, there is a major concern about the efficiency of food manufacturing lines due to higher pumping power and operational cost required to transfer the fluid in processing facilities (Viswanath et al ., 2007; Amamcharla et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%